Effect of KMnO4 on shelf life and quality of banana (Musa paradisiaca L.) - Dhakal, Smriti; Aryal, Sujata; Khanal, Prakash; Basnet, Babi; Srivastava, Arvind (Fundamental and Applied Agriculture, 2021)
Banana being a climacteric fruit shows an increase in ethylene production during the ripening which reduces the shelf life. Potassium permanganate (KMnO4) as an ethylene absorber extends the shelf life and maintains posthar- vest quality. The experiment was conducted at the laboratory of Nepal Poly- technic Institute, Bharatpur-11, Chitwan, Nepal from 2nd August to 13th August 2018 to investigate the effect of different concentrations of KMnO4 on post-harvest qualities of banana at ambient conditions (30.35 ± 2.15 °C and 82 ± 5.5% RH). The experiment consisted of five different concentrations of KMnO4 viz. 0, 2, 4, 6 and 8 grams (g) per seven fingers of banana. The research was laid out in a Complete Randomized Design (CRD) with four replications. Among different concentrations of KMnO4, 4 g KMnO4 showed the minimum weight loss on 4, 8 and 12 days which was 0.66%, 2.55% and 5.93% respectively. The maximum shelf life (13.50 days), titratable acidity (1.89%) and firmness (4.47 lb) was recorded in 6 g KMnO4. The highest total soluble solids (18.30%) was obtained in 0 g KMnO4. Thus at ambient room conditions (30.35 ± 2.15 °C and 82 ± 5.5% RH), it is suggested to use 6 g KMnO4 per seven fingers of banana fruits to reduce post-harvest loss.